2016
DOI: 10.1038/cddis.2015.328
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HDAC with a novel inhibitor effectively reverses paclitaxel resistance in non-small cell lung cancer via multiple mechanisms

Abstract: Chemotherapy paclitaxel yields significant reductions in tumor burden in the majority of advanced non-small cell lung cancer (NSCLC) patients. However, acquired resistance limits its clinical use. Here we demonstrated that the histone deacetylase (HDAC) was activated in paclitaxel-resistant NSCLC cells, and its activation promoted proliferation and tumorigenesis of paclitaxel-resistant NSCLC cells in vitro and in vivo. By contrast, knockdown of HDAC1, a primary isoform of HDAC, sensitized resistant cells to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 35 publications
0
74
0
2
Order By: Relevance
“…In fact, a very recent study showed that treatment of paclitaxel-resistant lung cancer cell line with a novel HDACi sensitized the cells to paclitaxel-induced cytotoxicity both in vitro and in vivo. 58 Synergy between taxanes and HDACi in inducing cytotoxicity has been previously demonstrated in vitro and in xenograft tumor models of ovarian, breast, and prostate cancer. 30,[59][60][61][62][63][64][65][66][67][68] Belinostat has been found to be synergistic with taxanes in inducing apoptosis in prostate and ovarian cell lines and in clinical samples from ovarian tumors grown in organoid culture.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, a very recent study showed that treatment of paclitaxel-resistant lung cancer cell line with a novel HDACi sensitized the cells to paclitaxel-induced cytotoxicity both in vitro and in vivo. 58 Synergy between taxanes and HDACi in inducing cytotoxicity has been previously demonstrated in vitro and in xenograft tumor models of ovarian, breast, and prostate cancer. 30,[59][60][61][62][63][64][65][66][67][68] Belinostat has been found to be synergistic with taxanes in inducing apoptosis in prostate and ovarian cell lines and in clinical samples from ovarian tumors grown in organoid culture.…”
Section: Discussionmentioning
confidence: 94%
“…HDAC inhibitors are reported to enhance the anti-tumor activities of other chemotherapeutic agents [5,6]. Various clinical trials of combination therapies of HDAC inhibitors have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…A549-CHI-R cells, which exhibit enhanced HDAC activity, demonstrated cross-resistance to GEM, TAX and VNR in the present study. Consistent with this, paclitaxel-resistant NSCLC cells exhibited enhanced HDAC activity and tumorigenicity (36). Increased HDAC1 expression in NSCLC tissue predicted a poor prognosis for patients treated with paclitaxel (36).…”
Section: Discussionmentioning
confidence: 67%
“…Consistent with this, paclitaxel-resistant NSCLC cells exhibited enhanced HDAC activity and tumorigenicity (36). Increased HDAC1 expression in NSCLC tissue predicted a poor prognosis for patients treated with paclitaxel (36). TAX and VNR are microtubule-targeting drugs; their most potent cytotoxic action is the suppression of microtubule dynamics, leading to mitotic arrest and subsequent cell death (37).…”
Section: Discussionmentioning
confidence: 89%